Oxytocin Role S in Neurodegenerative Disorders and Treatment - Hasan A. M. M. Almansoub, (Enhanced Knowledge in Sciences and Technology, 2022)
Oxytocin is a nonapeptide that is incorporated in the cell bodies by the supraoptic (SON) nuclei and hypothalamic paraventricular (PVN). Magnocellular oxytocin neurons of these nuclei innervate different forebrain regions and release oxytocin into the blood from the posterior pituitary. Like other neuropeptides, Oxytocin has been determined to work a critical role in the regulation of many behaviors connected with neuropsychiatric disorders, including social memory response to social stimuli, social interactions, feeding behavior, decision making in the context of social interactions, emotion alloreactivity, etc. Oxytocin may additionally exert important leadership in hippocampal synaptic plasticity, circadian rhythms, autonomic responses, antinociception, and motoneuron excitability. Accordingly, there is a medical care in its potential oxytocin therapeutic use for the treatment of neurodegenerative diseases associated with fear, anxiety, depression, memory and learning and social dysfunctions, posttraumatic stress disorder, generalized anxiety disorder, and social anxiety disorder, as well as autism, Parkinson disease, Alzheimer disease, and schizophrenia. In this review, the researchers highlighted many recent studies about oxytocin play essential roles in neurodegenerative diseases and potential therapy.